2021
DOI: 10.17507/tpls.1106.05
|View full text |Cite
|
Sign up to set email alerts
|

English for General Academic Purposes or English for Specific Purposes? Language Learning Needs of Medical Students at a Chinese University

Abstract: The debate over the appropriacy of EGAP and ESP has been an ongoing concern in many higher education contexts. In this paper we discuss how teachers’ and students’ perceptions of English curriculum needs are reflected in the conflict between short-term goals, such as passing exams, and long-term goals, such as career development. Students, doctors and teachers at a medical university in the central part of China were asked about their needs through questionnaires and structured interviews. The findings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…To ensure a successful transition to ESP, it is necessary to overcome certain issues among stakeholders. In the case of students, there is a conflict between short-term and long-term expectations (Li & Heron, 2021). On the one hand, they are keen to pass compulsory English courses as soon as possible to focus on other areas of study.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…To ensure a successful transition to ESP, it is necessary to overcome certain issues among stakeholders. In the case of students, there is a conflict between short-term and long-term expectations (Li & Heron, 2021). On the one hand, they are keen to pass compulsory English courses as soon as possible to focus on other areas of study.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Several researchers have argued in favor of replacing EGAP with ESP. In Li and Heron's (2021) study, first-and third-year medical students from a Chinese university claimed that EGAP only catered to mediocre students and could not meet the needs of more advanced students such as those who already obtained adequate scores in IELTS. Some participants even viewed EGAP as an impediment to their English learning.…”
Section: English Education In Chinese Medical Schoolsmentioning
confidence: 99%
“…The need for high levels of English proficiency is particularly pronounced among medical students in the Chinese context. Previous studies have indicated that medical students must possess adequate English proficiency to navigate scientific journals, to stay updated with global medical advancements, and to publish their own empirical work in prestigious journals indexed by the Science Citation Index (SCI) (Li & Heron, 2021;Deng et al, 2022). Moreover, English proficiency has gained significant weight in the selection process for graduate school admissions in China, evident through the inclusion of an English testing segment in graduate school application procedures, such as the Postgraduate Admission Test and graduate school interviews.…”
Section: Introductionmentioning
confidence: 99%
“…A needs analysis study was done by Li and Heron (2021) that aimed to investigate the language learning needs of medical students at a Chinese university regarding the choice between English for General Academic Purposes (EGAP) and English for Specific Purposes (ESP). The primary objectives of the study were to determine whether medical students prefer Medical English courses taught from the early years of university education and whether incorporating medical texts in the curriculum facilitates the development of medical English proficiency from the first year of study.…”
Section: Literature Reviewmentioning
confidence: 99%